2020
DOI: 10.2147/jep.s273120
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antiviral Effects of Oleandrin</p>

Abstract: Over the past 15 years, investigators have reported on the utility and safety of cardiac glycosides for numerous health benefits including those as treatments for malignant disease, stroke-mediated ischemic injury and certain neurodegenerative diseases. In addition to those, there is a growing body of evidence for novel antiviral effects of selected cardiac glycoside molecules. One unique cardiac glycoside, oleandrin derived from Nerium oleander , has been reported to have antiviral acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 86 publications
0
21
0
Order By: Relevance
“…3 Oleandrin is a derivative of the plant Nerium oleander, an ornamental shrub native to Northern Africa, the Eastern Mediterranean Basin, and Southeast Asia. 16,17 Oleandrin is a cardiac glycoside with structures and action similar to those of digoxin. [18][19][20][21] Cardiac glycosides work by inhibiting the enzyme, Na+/K+ ATPase, in the membrane of cardiac myocytes.…”
Section: Oleandrinmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Oleandrin is a derivative of the plant Nerium oleander, an ornamental shrub native to Northern Africa, the Eastern Mediterranean Basin, and Southeast Asia. 16,17 Oleandrin is a cardiac glycoside with structures and action similar to those of digoxin. [18][19][20][21] Cardiac glycosides work by inhibiting the enzyme, Na+/K+ ATPase, in the membrane of cardiac myocytes.…”
Section: Oleandrinmentioning
confidence: 99%
“…[18][19][20][21] Cardiac glycosides work by inhibiting the enzyme, Na+/K+ ATPase, in the membrane of cardiac myocytes. [17][18][19][20][21] This ultimately leads to an accumulation of intracellular calcium, and these changes in calcium concentration result in increased cardiac inotropy and decreased chronotropy. 20,21 Poisoning by ingestion of this plant is a common toxicological emergency in tropical and subtropical parts of the world and intentional self-harm following ingestion is prevalent in South Asian countries.…”
Section: Oleandrinmentioning
confidence: 99%
“…These data will be reported in a follow up study. The list of specific enveloped viruses, now including SARS-CoV-2, against which oleandrin and extracts containing this molecule have been shown to be effective continues to expand [20] . As such, consideration of this re-purposed cardenolide as a safe and effective antiviral agent with its unusual ability to reduce progeny viral infectivity should be given serious further consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Less appreciated is the antiviral activity of this class of compounds. Recent reviews have described antiviral activities of cardenolides, such as oleandrin, against cytomegalovirus, Herpes simplex virus, adenovirus, chikungunya virus, coronaviruses, respiratory syncytial virus, Ebola virus, influenza virus and human immunodeficiency virus [19] , [20] . We recently reported that oleandrin also has strong antiviral activity against HIV-1 and HTLV-1 [21] , [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Ellagic acid, myricetin, and some other phytochemicals ( Setlur et al, 2017 ) as anti-Ebola compounds act through inhibiting virus entry ( Cui et al, 2018 ) and RNA interaction, respectively ( Daino et al, 2018 ). An in vitro antiviral effect of oleandrin acts as a novel cardiac glycoside against the EBOV ( Newman et al, 2020 ). Some preclinical evidence suggests the effectiveness of cannabinoids in viral diseases ( Mabou Tagne et al, 2020 ).…”
Section: Ebovmentioning
confidence: 99%